Implementasi Identitas Kependudukan Digital (IKD) di Kota Tangerang: Analisis Implementasi Kebijakan Model George C. Edwards III - Rifatul Hasanah; Riny Handayani (PUBLICNESS: Journal of Public Administration Studies, 2025)
The low activation rate of the Digital Population Identity (IKD) remains a challenge in the digitalization of population administration at the local level. In Tangerang City, IKD activation reached only 2.06% (28,173 users) in 2023 and increased to 4.45% (62,364 users) in 2024, which is still far below the national target of 25%. This study aims to analyze the implementation of the IKD program in Tangerang City using George C. Edwards III’s policy implementation model, which includes the aspects of communication, resources, disposition, and bureaucratic structure. This research employs a qualitative approach with data collection techniques consisting of in-depth interviews, observation, and documentation involving policy implementers as well as IKD users and non-users. The findings indicate that communication among policy implementers has functioned relatively well; however, public communication remains uneven and has not been able to enhance public understanding and trust. Human resources, facilities, and technological support are considered adequate, but transparency regarding personal data security remains a major weakness. The disposition of implementers reflects positive attitudes, yet it has not produced a meaningful impact on increasing public participation. The bureaucratic structure has supported implementation through clear coordination, although it has not been strengthened by specific local standard operating procedures. The novelty of this study lies in the finding that the low level of IKD activation is more strongly influenced by limitations in policy communication and low public trust in data security rather than by technical factors alone.